Influence of Quality of Mounting Process of RF Transistors on Their Thermal Parameters and Lifetime - Krzysztof Górecki; Wojciech Kowalke; Przemysław Ptak (Applied Sciences, 2022)
The paper presents the results of investigations illustrating the influence of imperfections in the soldering process on thermal properties of transistors operating in RF (Radio Frequency) systems. The methods of measurements used to determine the junction and case temperature of the tested transistors and their thermal resistance are described. The results of the performed measurements are presented and discussed, and their statistical analysis is carried out. The correlation between thermal parameters of the tested transistors, parameters of the assembly process and the measurement conditions is investigated. Some calculation results illustrating an influence of device thermal resistance and dissipated power on changing its lifetime are shown and discussed. It is also shown that no correlation between the void sizes and the device thermal resistance and lifetime is observed. Possibilities of improving the assembly process are indicated, which allows extending the expected lifetime of the tested transistors.